Seleção de recursos por duas espécies de besouros bruquíneos do gênero gibbobruchusna planta hospedeira bauhinia curvula benth - Bergamini, Leonardo Lima (2013)
The process of host-plant selection is the main interface in the herbivore-plant interactions, with deep consequences for the ecology and evolution of those groups. In this work, we investigate some steps of the host-plant selection in two congeneric species of seed beetles. In the first chapter, we assess the oviposition pattern and larval survival in the seed-beetle G. cavillator to evaluate whether oviposition site choices maximize offspring survival, accounting for the spatially hierarchic structure of the system. In the second chapter, we analyze the fine-scale positioning of G. speculifer eggs, and explore the role of geometric constraints in the egg distribution patterns. Altogether our results exemplify how small differences in key traits of the host-plant selection can lead to significant differences in the interaction between herbivore insects and their host plants.